Handbook of Digital 3D Reconstruction of Historical Architecture - Münster, Sander; Apollonio, Fabrizio Ivan; Bluemel, Ina; Fallavollita, Federico; Foschi, Riccardo; Grellert, Marc; Ioannides, Marinos; Heinrich Jahn, Peter; Kurdiovsky, Richard; Kuroczynski, Piotr; Lutteroth, Jan-Eric; Messemer, Heike; et al. (My University, 2024)
This open access book is a handbook for students, experts and interested parties who want to learn more about digital 3D reconstruction of historical architecture. The book provides answers to the core questions of the subject: What is a digital 3D model or a digital 3D reconstruction? How are they created and what are they used for? Practical instructions, condensed knowledge, explanations of technical terms and references to example projects, literature and further references provide information of varying density and thus enable an individual introduction to the subject. The book combines extensive knowledge on the topic of "digital 3D reconstruction of historical architecture" and provides practical instructions for independent implementation. Up to now, there has been no cross-disciplinary vocabulary for technical terms in this field, so this publication makes a start.
Keywords: 3D Reconstruction; Digital Visualisation; Virtual Research Environments; Historical Architecture; 3D Modelling